Competição de impostos sobre serviços entre municípios brasileiros - Picin, Eric William (2015)
Currently, one of the funding sources of Brazilian municipalities is the taxes paid by companies of services sector and independent professionals taxable service providers. All of these taxes collected are consolidated and available in the Annual Report of Social Information (RAIS) database. From that database and with sociodemographic indicators, it’s possible to analyze concentrations, trends and a possible fiscal war among taxes of certain jurisdictions and his neighbors. So, the objective of this thesis is to verify the existence of a tax competition, migration of companies and the division of the jurisdiction. Thus there were developed three basic models. The first one tries to check the tax competition in Brazilian Municipalities, i.e. it seeks to determine the influence of the ISS, tax service rate, from neighboring municipalities in the specific municipality. The second deals with the migration of the companies, according to the race to the bottom methodology, studying the behavior of companies in relation with tax benefits. Finally, the last model addresses the emancipation of municipalities, analyzing if jurisdiction with high tax burdens for ISS, in relation to their neighbors, would be divided into two or more jurisdictions, equalizing the tax in the entire region. The results indicate the existence of tax competition in Brazilian municipalities and a certain probability of emancipation with respect of ISS of neighbor’s jurisdiction. However, according to the results, it’s impossible to say that exist migration of companies due to tax benefits.